In a Mouse Model of Sepsis, Hepcidin Ablation Ameliorates Anemia More Effectively than Iron and Erythropoietin Treatment. Issue 4 (October 2017) - Khorramian, Eeman; Fung, Eileen; Chua, Kristine; Gabayan, Victoria; Ganz, Tomas; Nemeth, Elizabeta; Kim, Airie
Abstract : ABSTRACT: Intensive care unit (ICU) anemia is an extreme version of anemia of inflammation that occurs commonly in critically ill patients and is associated with increased morbidity and mortality. Currently available therapies for ICU anemia have shown inconsistent efficacies in clinical trials. We conducted a systematic study of the effects of early versus delayed iron (Fe) and/or erythropoietin (EPO) therapy in our previously characterized mouse model of ICU anemia based on an injection of heat-killed Brucella abortus. To study the effects of ongoing inflammation on the response to therapy, inflamed wild-type (WT) and hepcidin knockout (HKO) mice were treated at either early (days 1 and 2) or delayed (days 7 and 8) time points after the inflammatory stimulus. In the early treatment group, Fe and/or EPO therapy did not increase hemoglobin (Hgb) levels or reticulocyte production in either the inflamed WT or HKO groups. In the delayed treatment group, combination Fe + EPO therapy did increase Hgb and reticulocyte production in WT mice (mean ΔHgb in WT saline group −9.2 g/dL vs. Fe/EPO −5.5 g/dL; P  < 0.001). The HKO mice in the delayed treatment group did not improve their Hgb, but HKO mice in all treatment groups developed a milder anemia than the WT mice. Our findings indicate that combination Fe + EPO therapy is effective in partially reversing ICU anemia when administered after the phase of acute inflammation. Hepcidin ablation alone was more effective in attenuating ICU anemia than Fe + EPO therapy, which indicates the potential of antihepcidin therapeutics in treating ICU anemia. Abstract : Supplemental Digital Content is available in the text